Association of Vitamin D Receptor Gene Single Nucleotide Polymorphism (ApaI) with Chronic Obstructive Pulmonary Disease (Eastern Medical College Journal, 2025)
Background: Association of Vitamin D receptor gene single nucleotide polymorphism and its association with various diseases have been previously researched, but its association with chronic obstructive pulmonary disease (COPD) has not been investigated yet.Objective: To evaluate the association between vitamin D receptor gene polymorphism (ApaI) and COPD.Methods: This study was conducted in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, from March 2019 to February 2020. For research, pulmonologists diagnosed 15 (fifteen) COPD patients with age 40 to 80 years (post-bronchodilator FEV1/FVC